SINTESIS CALKON ((E)-1,3-DI(NAPHTHALEN-2-YL)PROP-2-EN-1-ONE) DAN AKTIVITASNYA SEBAGAI ANTIOKSIDAN - Rahmiwati Hilma; Jasril -; Hilwan Yuda Teruna (Sistem Informasi, 2012)
Study on chalcone calkon (E)-1,3-di(naphthalen-2-yl)prop-2-en-1-one synthesis have been carried out with stirrer methode. These compounds can be used as intermediate compound to synthesize others compounds which was reported having antimicrobial, anti-inflammatory, anti-depressant, anti-tumour. The of chalcones synthesis vatives were reported in acid and alkali condition. In this study, chalcone and its derivates were synthesized by using stirrer method in alkaline condition in room temperature. the compounds subjected to somes analyses including melting point measurement, thin layer chromatography and HPLC. Scavenging free radical by using DPPH methode showed Scavenging free radical with LC50 >80 μg/ml min potent activity while the ascorbat acid LC50 89,79 μg/ml.